EFL STUDENTS’ PERCEPTIONS TOWARD QUIZIZZ AS AN ASSESSMENT TOOL DURING ONLINE LEARNING - Alvina Indana Zulfa; Devinta Puspita Ratri (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2022)
Assessment is an ongoing process on students’ learning achievement. It is not about giving students the value of numbers or letters; an assessment tool is used to measure and monitor students’ understanding of the material taught. Quizizz is a beneficial assessment tool with interactive features that can help students and teachers do the assessment during online learning. However, some students find difficulties in accessing Quizizz. Therefore, this research aims to investigate EFL students’ perceptions toward Quizizz as an assessment tool during online learning. This study involved 100 twelfth graders of one junior high school students in Malang, Indonesia. These students have experienced using Quizizz to do the assessment for four weeks. In this research, quantitative method with a survey research design was chosen. A close-ended questionnaire was used to collect the data on students’ perceptions about the efficacy, the benefit, and the challenges of using Quizizz, and the data were analyzed through descriptive statistics. The result of the study revealed that although there was an obstacle to fully implementing Quizizz, most of the students gave a positive attitude to the use of Quizizz as an assessment tool.